Alliances and treaties between Frankish and Muslim rulers in the Middle East : cross-cultural diplomacy in the period of the Crusades - Kohler, Michael. (The Muslim World in the Age of the Crusades, 2013)
In Alliances and Treaties between Frankish and Muslim Rulers Michael Köhler presents a fully integrated study of Frankish-Muslim diplomacy in the period from the First Crusade through to the thirteenth century. It is a ground-breaking study that challenges preconceived notions of the relations between Frankish and Muslim rulers in the Middle East. Commonly portrayed as an era of conflict, the period appears here as one in which conventions of diplomatic cooperation were commonplace. This book is one of the few works in the fields of Crusader Studies and Middle Eastern Studies that draws to the same extent on Arabic and Western sources; two textual traditions that have usually been studied in isolation from each other.